2020
DOI: 10.1007/s40617-020-00429-8
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Treatment Integrity in the Face of Crisis: A Treatment Selection Model for Transitioning Direct ABA Services to Telehealth

Abstract: With health care funders' increasing approval of telehealth service as an emergency measure to provide continuity of care during the COVID-19 crisis, practicing behavior analysts have an unprecedented opportunity to demonstrate that essential, medically necessary behavior-analytic services can be provided via telehealth in a manner that maintains treatment integrity and produces meaningful client outcomes. This telehealth treatment selection guide was designed to assist practicing behavior analysts in determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 9 publications
3
60
0
Order By: Relevance
“…Thus, although participants engaged in behaviors consistent with a bidirectional naming repertoire, overt echoics did not occur at high rates consistently across trials or sessions. Rodriguez (2020) suggested assessing client's attending, responsiveness to prompting, and frequency and intensity of challenging behavior to determine if a client would be appropriate for direct telehealth services. Participants in this study demonstrated high levels of attending during teaching trials (i.e., 93.8-100% per session), responded to vocal corrective feedback, and did not engage in frequent challenging behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, although participants engaged in behaviors consistent with a bidirectional naming repertoire, overt echoics did not occur at high rates consistently across trials or sessions. Rodriguez (2020) suggested assessing client's attending, responsiveness to prompting, and frequency and intensity of challenging behavior to determine if a client would be appropriate for direct telehealth services. Participants in this study demonstrated high levels of attending during teaching trials (i.e., 93.8-100% per session), responded to vocal corrective feedback, and did not engage in frequent challenging behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the child's repertoire, some behavior analysts and their supervisees are implementing clinical sessions directly with the child via Zoom™ or other video-based telecommunication platforms. That is, staff are conducting sessions virtually with the child, not necessarily training parents or another interventionist to implement behavior analytic procedures (Rodriguez, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, an expert 'hub' provides consultation about patients to providers ('spokes') through videoconferencing, empowering the local physicians to effectively care for complex patients (Arora et al 2011;Mazurek et al 2016). Efforts to provide targeted guidance for professionals working under these conditions are now being developed (Rodriguez 2020).…”
Section: Health Carementioning
confidence: 99%
“…Therefore, professionals have started to evaluate the feasibility and opportunity of a transition, at least temporarily, towards telehealth services to provide behavior analysis services. The therapist provides instructions to the client through the use of video-conferencing systems (Rodriguez, 2020).…”
Section: Introductionmentioning
confidence: 99%